The boy who followed Ripley - Highsmith, Patricia, 1921-1995 (Highsmith, Patricia, 1921-1995. Ripley, 2008)
Highsmith explores Ripley's bizarrely paternal relationship with a troubled young runaway, whose abduction draws them into Berlin's seamy underworld.